Quinoxalinone as a Privileged Platform in Drug Development - Shi, Leilei; Hu, Wei; Wu, Jifeng; Zhou, Huaiyu; Zhou, Hua; Li, Xun (Mini Reviews in Medicinal Chemistry, 2018)
Among the family of nitrogen-containing heterocycles, quinoxalinone (or quinoxalin-2-one) core, characterized by pyrazin-2(1H)-one fused to benzene ring at two adjacent carbon atoms, has been frequently found in a variety of pharmacologically active compounds with biological or pharmaceutical applications. It was gratifying that a larger part of these bioactive quinoxalinone-based derivatives has entered various clinical trials, which in turn hastens the synthetic versatility and also initiates various derivatization of quinoxalinone scaffold. In this review, we highlighted the newly emerged quinoxalinone- based derivatives or analogues, with the emphasis of their biological applications and structure-activity analysis covering literatures in recent years.
Keywords: biological activities